Theology and Innovation in Contemporary Galicia - Varela Tembra, Juan José (2022)
The aim of this contribution is to bring the reader closer to the research and teaching developed in Galicia within the scope of Theology. A science, which has a fundamental purpose, since theology itself as a discipline of knowledge must foster relationships between faith and culture, to promote a cultural and social profusion that enriches a society in continuous change. The development of the theological work, both teaching and research, within the originality of Galicia is linked both to the ecclesial and cultural tradition and to theology itself as an academic discipline. Such work shares, to a large extent, the same peculiarities as the rest of the Spanish state and Portugal, with the just disparities of the precise names that support them and the environments in which they are carried out.